Impact of Combined Antiretroviral Therapy on Metabolic Syndrome Components in Adult People Living with HIV: A Literature Review - Mariusz Sapuła; Magdalena Suchacz; Andrzej Załęski; Alicja Wiercińska-Drapało (Viruses, 2022)
The development of metabolic derangements as a result of HIV treatment has been an important area of research since the introduction of zidovudine in the 1980’s. Antiretroviral therapy has intensely evolved in the last three decades, with new drugs gradually incorporated into everyday clinical practice. With the life expectancy of people living with HIV rapidly approaching that of their HIV-negative counterparts, the influence of these antiretrovirals on the development of the components of the metabolic syndrome remains of major interest to clinicians and their patients. In this review, we aimed to discuss the impact of cART on components of the metabolic syndrome, i.e., weight, plasma lipid levels, plasma glucose levels, and blood pressure, describing the influence of cART classes and of individual antiretrovirals. We also aimed to outline the limitations of the research conducted to date and the remaining knowledge gaps in this area.